Enhancing athlete performance under pressure: the role of attribution training in mitigating choking - Dan Huang; Dan Huang; Huilin Wang; Yiwei Tang; Hanyue Lei; Denise Koh (Frontiers in Psychology)
IntroductionChoking in athletes describes a marked reduction in their skill level, falling below the normal level, when under stress. This paradoxical performance decline, which athletes strenuously to avoid yet frequently encounter, was the focus of this study. We implemented training interventions on athletes who had experienced choking to assess their impact on fear of failure and self-criticism. Correct or improve the subjects’ inappropriate attribution of failure results, and enable them to learn to use appropriate and positive attribution, enhance motivation levels, and thus achieve the purpose of improving behavior and performance levels.MethodsThe snowball sampling technique was used to collect data through the combination of online electronic questionnaires and offline paper questionnaires, so as to explore the choking phenomenon of elite athletes by attributing the influence of training variables on self-efficacy. The research team conducted a survey of elite athletes in Central China between October and December 2023. In this study, 350 questionnaires were distributed, 350 questionnaires were collected after the questionnaires were distributed, and 328 valid questionnaires were finally eliminated through screening. And the relevant statistical analysis is carried out on the data.ResultsThe results confirmed the significant correlations between attribution training and fear of failure (β = −0.548, p < 0.001), attribution training and self-criticism (β = −0.531, p < 0.001), fear of failure and self-efficacy (β = −0.240, p < 0.001), and self-criticism and self-efficacy (β = −0.408, p < 0.001). Finally, the correlation between fear of failure and self-criticism (β = −0.211, p < 0.01) was validated.ConclusionAthletes who underwent attribution training showed significant reductions in fear of failure and self-criticism, thereby decreasing their negative emotions, enhancing their positive emotions, and improving their self-efficacy during sports performance.